Numerical analysis of the elastic response of a floating collar in waves. (1st February 2015) - Zhao, Yun-Peng; Bai, Xiao-Dong; Dong, Guo-Hai; Bi, Chun-Wei; Gui, Fu-Kun
Abstract: Gravity-type fish cages are playing an increasingly important role in fishery aquaculture. As the main load-bearing component of gravity-type fish cages, the floating collar supports the whole cage and undergoes large deformations. In this paper, a numerical method is developed to study the motions and elastic deformations of an HDPE floating collar in waves. The governing equations of motions are established by Newton׳s second law, and those governing the deformations are obtained according to the curved beam theory and the modal superposition method. Damping of the elastic deformations is introduced and analysed in detail to improve the numerical model. To validate the numerical model, a series of physical model tests are conducted. Good agreement between the numerical and experimental data is obtained. The numerical results indicate that the in-plane and out-of-plane deformations calculated using the first four modes yield satisfactory precision. The positions of the maximum deformations in different wave propagation directions and the effect of the forms of the mooring line arrangement have also been investigated. The numerical results show that the four-point-mooring cage is more reliable than the single-point-mooring cage. The endpoints of the diameters that are parallel or perpendicular to the wave direction have the largest deformation. Highlights: The motions and deformations of the floating collar are studied using a numerical method. The damping effect on the numerical model is discussed in details and the modified models of the elastic deformations are given. The position of maximum deformations of the floating collar and the effect of the mooring line arrangements are investigated.